A shoulder surfing resistance using graphical authentication system - N, Rupavathy; Mary Belinda M. J, Carmel; G, Nivedhitha (International Journal of Engineering and Technology, 2018)
Authentication supported passwords is employed mostly in applications for laptop security and privacy. However, human actions like selecting unhealthy passwords and inputting passwords in an insecure approach are considered “the weakest link” within the authentication chain. Instead of impulsive alphanumerical strings, users tend to decide on passwords either short or purposeful for simple learning. With internet applications and mobile apps piling up, individuals will access these applications any time and any place with  numerous devices. This evolution brings nice convenience however additionally will increase the chance of exposing passwords to shoulder surfing attacks. Attackers will observe directly or use external recording devices to gather users’ credentials. To overcome this drawback, we tend to plan a unique authentication system Pass Matrix, supported graphical passwords to resist shoulder surfing attacks. With a one-time valid login indicator and circulatory horizontal and vertical bars covering the  complete scope of pass-images, Pass Matrix offers no hint for attackers to work out or slim down the password even they conduct multiple camera-based attacks. We tend to additionally enforce a Pass Matrix image on android and applied real user experiments to judge   its memorability and usefulness. From the experimental result, the proposed system achieves higher resistance shoulder surfing attacks whereas maintaining usability.
Keywords: Privacy; Security; Authentication; Surfing